(untitled) (Bangladesh Journal of Pharmacology, 2014)
The present study was undertaken to evaluate antihyperlipidemic effect of aqueous methanolic extract of Berberis orthobotrys in experimentally induced hyperlipidemic animal models. Atorvastatin was used as standard drug. The crude extract (50 and 100 mg/kg) significantly prevented the increase in low density lipoprotein (LDL), very low density lipoprotein (VLDL), total cholesterol (TC), triglyceride (TG), atherogenic index and coronary risk index in high fat diet, cholesterol, fructose and olive oil-induced hyperlipidemic rat models whereas in ethanol treated mice, the extract reduced VLDL, TG and TC levels. The high density lipoprotein (HDL) level was significantly increased in high fat diet, olive oil and cholesterol induced hyperlipidemic rats. The reduction in serum level of above parameters with 100 mg/kg dose of extract was comparable with atorvastatin. It is concluded that B. orthobotrys has atheroprotective and lipid lowering potential.